Perilaku Menyimpang Mahasiswi yang Bekerja sebagai Pemandu Karaoke di Kota Jember - Pratami, Meilya Yolanda; Gianawati, Nur Dyah (e-Sospol, 2019)
Abstract This study aimed to explain by describing what and how far the deviant behavior of female students working as LC (Ladies Companion) in Jember. The study was conducted with a qualitative approach and belonged to a descriptive research. The research subjects were students who worked as LC. The analysis unit used a purposive technique. The data collection was supported through observation, interviews, and documentation. Furthermore, the explanation was done descriptively to explain the students' behavior who work as LC. Based on the research that has been done, it was found that the behavior of the students who work as LC were drinking alcoholic beverages, using narcotics and drugs, even doing prostitution. The occurrence of these deviant behaviors will potentially be a social disease that can lead to social problems in the community and if it is not immediately addressed, it will lead to social disorganization. Indirectly, the deviant behavior done by female students working as LC becomes a social problem in the community.